Phikud navakot extract acts as an ER stress inhibitor to ameliorate ER stress and neuroinflammation. - Temviriyanukul, P.; Chansawhang, A.; Inthachat, W.; Supasawat, P.; Phochantachinda, S.; Pitchakarn, P.; Chantong, B. (Heliyon, 2024)
The prevalence of neurological disorders (NDs) such as Alzheimer's disease (AD) is increasing globally, and the lack of effective pharmacological interventions presents a significant health risk. Multiple mechanisms including the activation of oxidative stress, amyloid pathway, ER stress, and neuroinflammation have been implicated in AD; therefore, multi-targeted agents against these mechanisms may be preferable to single-target agents. Phikud Navakot (PN), a Thai traditional medicine combining nine herbs, has been shown to reduce oxidative stress and neuroinflammation of neuronal and microglia cells and the coculture between them, indicating the promising role of PN extract as anti-AD. This study evaluated the neuroprotective effects of PN extract against oxidative stress, amyloid pathway, endoplasmic reticulum stress (ER stress), and neuroinflammation using neuronal and microglia cells, as well as in a Drosophila model of AD. Results showed that PN extract reduced oxidative stress, lipid peroxidation, pro-inflammatory cytokines, amyloid pathway, and ER stress induced by aluminum chloride (AlCl3, AD-induced agent) or thapsigargin (TG, an ER stress activator) in both neurons and microglia cells. PN extract also reduced oxidative stress, ER-stress-related genes, and neurotoxic peptides (amyloid beta) in a Drosophila model of AD. Data indicated that PN extract may function as an anti-AD agent by targeting multiple mechanisms as described. This research also revealed for the first time that PN extract acted as an ER stress inhibitor.